Implementasi Metode Ḥiwar Qurani Untuk Meningkatkan Prestasi Belajar Siswa Dalam Bidang Studi Akidah Akhlak - Sodikin, Ikin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is motivated by PAI learning which is still delivered with an inappropriate method. So that Islamic Religious Education in schools is still limited to a learning routine in the classroom, namely just listening to monotonous lectures, doing assignments (PR), worship practices (prayer, reading the Qur'an and others), which focuses more on the development of intellectual aspects. only (level of knowledge). The purpose of this study is to improve the teacher's ability to make lesson plans (RPP), to know the implementation, learning achievement, and to know the effect of the hiwar qurani method in the field of study of aqidah morals. The method used in this research is classroom action research with the hiwar qurani method. The results showed that the average of the first cycle of the first action was 60.74, the second cycle of the second action was 64.44, the second cycle of the first action was 72.96, and the second cycle of the second action increased to 77.41. Meanwhile, student achievement based on the post test results after using the iwār jadalī method in learning Akidah Akhlak, the average value of the first cycle of the first action was 64.07, the second cycle of the second action was 70.37, the second cycle of the first action was 80.37, and the second cycle of the second action II the second action increased to 86.30. This shows that the hiwar qurani method can improve learning achievement in the field of moral creed.